Effects of Bacillus thuringiensis Genetic Engineering on Induced Volatile Organic Compounds Emission in Maize and the Attractiveness to a Parasitic Wasp - Xu, Hao; Wang, Xiaoyi; Chi, Guoliang; Tan, Bingchang; Wang, Jianwu (Frontiers in Bioengineering and Biotechnology, 2019)
In order to control lepidopteran and coleopteran insects, the genes expressing Bacillus thuringiensis (Bt) insecticidal proteins have been transferred into crops. Ecological risk assessments of the transgenic plants have included impacts on non-target entomophagous insects, such as parasitoid wasps. Herbivore-induced plant volatiles are considered to be important defensive traits of plants because these compounds play as an important role in recruitment of natural enemies. Here, we evaluated induced volatile emissions of maize seedlings of two Bt cultivars (5422Bt1, event Bt11 and 5422CBCL, event Mon810), and their nearly isogenic non-Bt line 5422. We damaged plants mechanically and then applied with the regurgitant of Spodoptera litura (F.) caterpillars (Lepidoptera: Noctuidae), or treated the plants with the plant hormone jasmonic acid (JA), to trigger similar defensive responses of plants. Compared to the non-Bt isoline 5422 and the Bt maize 5422CBCL, the other Bt maize 5422Bt1 released more (3E)-4,8-dimethyl-1,3,7-nonatriene (DMNT) when they were all treated by artificial wounds and caterpillar regurgitant; and released more linalool, DMNT and (E)-β-farnesene when applied with JA solution. As a result, the total volatile emission of the 5422Bt1 was highest. However, the difference in volatile emission did not affect the attractiveness of the Bt maize plants to the egg parasitoid Trichogramma ostriniae Pang et Chen (Hymenoptera: Trichogrammatidae) compared to the nearly isogenic non-Bt plants. The variability of induced volatiles of maize cultivars derived from conventional breeding programs and transgenic methods are discussed.